Estetika Sastra Populer dalam Film Remake Aladdin (2019) Produksi Disney - Rizki Eka Putri Alda (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2020)
This study aims to elaborate formulas in the movie Aladdin. The theories are the cultural production arena by Bourdieu and Disney's "princess" movie formula. This study used a qualitative descriptive method, with library research techniques as technique of collecting data. There are two data sources. The primary data which was the movie Aladdin and secondary data is the theories. The data analyzed by rereading and using the secondary data as the perspectives. The data will be presented specifically in form of words and narratives. The result of this study showed that Aladdin was a popular product that can be proved by the movie’s income which labeled box office and the movie also was the 5th successful remake movie. The success of the movie cannot be happened without the Disney marketing strategy, they knows how to analyze the market demand at time. In the Aladdin movie there was the same movie’s formulas as the other Disney’s but it was showed the feminism’s atmosphere too. Like, in the Jasmine’s characters, how the story end, the song with feminism nuances and also Jafar as the male villain was eliminated the stigma of an evil character that used to play by female characters.